α-Amylase Inhibition Activities by Flavonoid Compounds from Panda Plants (Kalanchoe tomentosa) - Lilis Siti Aisyah; Delia Ilfani; Faridia Puspita Lestari; Yenny Febriani Yun (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Diabetes mellitus (DM) is one of the major health problems. One way to deal with diabetes mellitus is by inhibiting the work of enzymes that hydrolyze carbohydrates, thereby reducing glucose absorption. The enzyme that plays a role in the breakdown of starch into simple sugars is the α-amylase. The genus Kalanchoe or Panda plant has been widely reported to contain a variety of secondary metabolites that have several activities such as antimalarial, antibacterial, antidiabetic, and anticancer potential. This study aims to isolate, determine the chemical structure, and test the inhibitory activity of α-amylase from the ethyl acetate fraction of K. tomentosa leaves. The isolation stage began with the maceration process with n-hexane and fractionated with ethyl acetate. Ethyl acetate extract was refracted using a gradient liquid vacuum chromatography (KCV) method (n-hexane: ethyl acetate: methanol). Repeated gravity columns separated the fraction of KCV results and preparative thin-layer chromatography (TLC-P) to obtain isolate pure. Isolate pure was characterized using several spectroscopic methods, including UV-Vis, IR, NMR. Determination of the structure of the compound against isolate pure shows that this isolate is a 3,7,4’-trihydroxyflavonol or kaempferol compound. The results of the test activity of 3,7,4’-trihydroxyflavonol compounds in inhibiting the enzyme α-amylase in vitro showed an IC50 value of 346 µU/mL. The results obtained indicate that the IC50 value is higher than that of the Acarbose, which was 39.3 µU/mL.